2019
DOI: 10.3390/su12010324
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Gaps with Respect to GM Non-Food Crops and GM Food Crops and Confidence in the Government’s Management of Biotechnology: Evidence from Beijing Consumers, Chinese Farmers, Journalists, and Government Officials

Abstract: Most soybean oil consumed in China is made from imported genetically modified (GM) soybeans, while livestock are fed imported GM soy meal and GM corn. However, no GM food crops are allowed to be planted in China at present. That puts China in a confusing situation where GM foods can be eaten but cannot be grown. Many studies suggest that it is partially due to Chinese consumers’ and government officials’ opposition to GM technology. This is the first study that examines different stakeholders’ and journalists’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Numerous studies have indicated that confidence in the government management of biotechnology plays a critical role in the attitudes toward GM foods and commercialization of GM crops. 7 For example, Zhao et al 40 indicated that confidence in the government management of GM food labeling significantly influenced Chinese consumers’ attitudes toward labeled GM products. However, our results show more than four fifths of consumers have no confidence in the government management of biotechnology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have indicated that confidence in the government management of biotechnology plays a critical role in the attitudes toward GM foods and commercialization of GM crops. 7 For example, Zhao et al 40 indicated that confidence in the government management of GM food labeling significantly influenced Chinese consumers’ attitudes toward labeled GM products. However, our results show more than four fifths of consumers have no confidence in the government management of biotechnology.…”
Section: Resultsmentioning
confidence: 99%
“…This method has been widely employed in agricultural economics, such as Yu et al (2020). 7 To minimize the bias of desirability bias, before filling out the questionnaire, the respondents were promised with the anonymity of the investigation and they were asked to complete the survey solely based on their own experiences. Moreover, the self-administered survey for data collection helps minimize the leading question bias and wording bias.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…As a fast developing country, China is the largest consumer and importer of genetically modified (GM) soybean [ 1 ]. The import of soybeans to China reached more than 95 million tons in 2017, which were used as processing materials [ 2 ]. Chinese consumers oppose GM foods due to their concerns about food safety [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome editing provides agriculture productivity for the world population, which has reached 7.8 billion and is estimated to exceed 10 billion by 2055 ( FAO, 2017 ; Li and Yan, 2020 ). Up until 2018, GE crops have been planted approximately 191.7 million acres throughout 26 countries and adopted by approximately 17 million farmers ( Yu et al, 2019 ; Przezbórska-Skobiej and Siemiński, 2020 ). The legal status between genetically modified organisms (GMO) and genome-edited products is still in discussion.…”
Section: Introductionmentioning
confidence: 99%